Flavor anomalies, the 750 GeV diphoton excess, and a dark matter candidate - Bauer, Martin; Neubert, Matthias (Physical review, 2016)
We argue that the diphoton excess recently reported by ATLAS and CMS can be explained, along with several anomalies seen in the flavor sector, in models where a Standard Model singlet scalar resonance with mass MS≈750 GeV is produced in gluon fusion via loops containing a scalar color-triplet leptoquark ϕ. For a leptoquark mass Mϕ≲1 TeV, the production cross section is naturally in the 10 fb range. A large S→γγ branching ratio can be obtained by coupling the scalar S to new color-singlet fermions χ with electroweak scale masses, which can be part of an SU(2)L multiplet, whose neutral component has the right mass and quantum numbers to be a dark matter candidate. Our model reveals a connection between flavor anomalies, the nature of dark matter and a new scalar, which acts as a mediator to the dark sector. The loop-mediated decay S→τ+τ− could be a striking signature of this model.